INFLUENCE OF EMPOWERMENT TOWARDS TURNOVER INTENTION, WITH JOB ATTITUDE MEDIATION (STUDY AT MITRAMAS JANGKAR LAKSANA COMPANY) - Alfonsus, Yohanes; Atmaja, Maristya Tri (Universitas Esa Unggul, 2016)
AbstractEmpowerment is the delegation of authority from superiors to subordinates in accordance with the functions and capabilities of each. Job attitude is learning is done with an object responds well consistently. Job attitude in this study is a combination of two constructs, Organizational Commitment and Job Satisfaction expected to provide a positive job attitude. Turnover Intention is the intention of the inside of employees to change jobs. These three things are important to study because it is an important part of human resource management strategy which aims to produce competent human resources and superior. The purpose of this study is to see the impact of the empowerment of turnover intentions, to see the effect of empowering the job attitude and the latter is viewed effect the empowerment of turnover intentions. This research is a quantitative study using SEM (Structural Equational Models) as statistical analysis. The use of SEM is to be able to measure with greater clarity and detail to what the objectives of the research can be achieved. After data retrieval, it can be concluded from this study is that empowerment does not affect positively to lower employee turnover intentions. Empowerment in this study influence to improve employee attitudes in a positive way, but the work attitude has no effect to lower employee turnover intentions.Â Keywords: Empowerment, Turnover Intention and Job Attitude